2020
DOI: 10.1177/1120672120929958
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery and dry eye disease: A review

Abstract: Aim To review published literature concerning cataract surgery and dry eye disease (DED). Methods A search was undertaken using the following: PubMed (all years), Web of Science (all years), Ovid MEDLINE(R) (1946 to 12 December 2019), Ovid MEDLINE(R) Daily Update 10 December 2019, MEDLINE and MEDLINE non-indexed items, Embase (1974–2019, week 49), Ovid MEDLINE (R) and Epub Ahead of Print, In-Process and Other Non-Indexed Citations and Daily (1946 to 12 December 2019), CENTRAL (including Cochrane Eyes and Visio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 137 publications
1
72
0
1
Order By: Relevance
“…In den letzten Jahren ist das Beschwerdenbild des Trockenen Auges immer mehr in das zentrale Tätigkeitsgebiet der Augenärzte gerückt. In zunehmenden Maβe werden unangenehme Benetzungsstörungen nach Operationen [1][2][3][4] und Strahlenbehandlungen [5] auch klinisch ernster genommen und behandelt [6]. Auch ist man sich der wirtschaftlichen Bedeutung einer angemessenen und effektiven Behandlung mehr als je zuvor bewusst [7,8].…”
Section: Themenschwerpunkt Einleitungunclassified
“…In den letzten Jahren ist das Beschwerdenbild des Trockenen Auges immer mehr in das zentrale Tätigkeitsgebiet der Augenärzte gerückt. In zunehmenden Maβe werden unangenehme Benetzungsstörungen nach Operationen [1][2][3][4] und Strahlenbehandlungen [5] auch klinisch ernster genommen und behandelt [6]. Auch ist man sich der wirtschaftlichen Bedeutung einer angemessenen und effektiven Behandlung mehr als je zuvor bewusst [7,8].…”
Section: Themenschwerpunkt Einleitungunclassified
“…More recent studies by Flaxman and co-workers and Bikbov and co-workers have not only confirmed this tendency, but forecasted further growth of cases [2,3]. Cataract surgery with intraocular lens (IOL) implantation has been quickly evolving over the years, with the development of new technology and techniques, such as phacoemulsification and new materials for IOL, making it a safer and more reliable procedure [4][5][6]. Following cataract surgery, few complications can appear, one of the most serious being in-the-bag-IOL dislocation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Children are easily rejected and alienated by other playmates in life because of strabismus (6); the occurrence of dry eye after surgery will further impact their mentality and follow-up treatment. On the other hand, the treatment of dry eye is a long-term process, and the clinical effect depends on the treatment compliance of children and their families (7). Therefore, exceptional nursing and follow-up during the treatment of children with dry eye after strabismus surgery, as well as the provision of additional care, will play a significant role in improving their treatment compliance and clinical effect.…”
Section: Introductionmentioning
confidence: 99%